METHODS OF LEARNING VOCABULARY IN PRIMARY GRADES - Sanobar ABDUMURATOVA (Scholar Express Journal, 2022)
Our country produced great thinkers who made an incomparable contribution to the development of world science. We must educate our youth to be enlightened and knowledgeable. The words "school education has a special place" should be an important program for all of us.
Keywords: classes; word; methodology; school